Green Methodologies for Copper(I)-Catalyzed Azide-Alkyne Cycloadditions: A Comparative Study - Marissa Trujillo; Clayton Hull-Crew; Andrew Outlaw; Kevin Stewart; Loren Taylor; Laura George; Allison Duensing; Breanna Tracey; Allen Schoffstall (Molecules, 2019)
Successful copper(I)-catalyzed azide-alkyne cycloaddition (CuAAC) reactions may be achieved by several methods. In this paper, four synthetic protocols were performed for direct comparison of time required for the synthesis, yield, and purity of the 1H-1,2,3-triazole products. The methods with Cu(I) catalysts were conventional, microwave heating, solvent-free, and a method using glycerol solvent. The compounds synthesized in this paper were known non-fluorinated triazoles and new fluorinated triazoles. The results lead to the conclusion that the microwave method should be strongly considered for CuAAC syntheses.